2018
DOI: 10.4025/cienccuidsaude.v17i3.42275
|View full text |Cite
|
Sign up to set email alerts
|

<b>Trajetória de casos de hanseníase e fatores relacionados/Trajectory of leprosy cases and related factors<b>

Abstract: Objetivou-se analisar a trajetória dos casos diagnosticados com hanseníase e os fatores relacionados, com enfoque nas ações de prevenção e controle preconizadas pelo Ministério da Saúde. Estudo transversal de natureza descritiva. Os dados foram coletados através de questionário estruturado em visitas domiciliares, com uso do programa Open Data Kit collect. Foram exportados, tratados e analisados no Statistical Package for the Social Sciences (SPSS®) v. 24. Para o cálculo do diagnóstico tardio considerou-se trê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In this scenario, it was observed an significant number of MB clinical forms, with a predominance of the borderline form, a finding consistent with several investigations (23)(24)(25)(26) and with the epidemiological panorama of 26% increase in these clinical forms over a decade in the country, reaching, in 2018, 77.2% of the detected cases (2) . Such results demonstrate that the bacillus transmission is active and refers to a critical node to be overcome by healthcare services, considering late diagnosis and treatment of the disease (22) .…”
Section: Discussionsupporting
confidence: 84%
“…In this scenario, it was observed an significant number of MB clinical forms, with a predominance of the borderline form, a finding consistent with several investigations (23)(24)(25)(26) and with the epidemiological panorama of 26% increase in these clinical forms over a decade in the country, reaching, in 2018, 77.2% of the detected cases (2) . Such results demonstrate that the bacillus transmission is active and refers to a critical node to be overcome by healthcare services, considering late diagnosis and treatment of the disease (22) .…”
Section: Discussionsupporting
confidence: 84%
“…The persistence and occurrence of new cases from long-standing and new infectious diseases, besides some transported among all participant countries like TB among HIVnegative and Malaria [13,14] become frequently issues to investigate. Moreover, leprosy is national diseases although there are no recent studies showed its prevalence among participant countries except Global Leprosy Strategy 2016-2020 named Accelerating towards a leprosy-free world was based on strengthening government ownership to stop leprosy and its complication [47]. Our study is the first to describe the significant effect of GNI to the evolution of mortalities caused by infectious diseases through the following hypothesis: Ho: The all means different is not significant and the alternative is that means different is significant at the 0.05 level, and Levene's and Brown-Forsythe test for homogeneity for variances.…”
Section: Discussionmentioning
confidence: 99%
“…The Levene's and Brown-Forsythe test showed that the new cases recorded on leprosy up to 2015 are almost the same in four countries (Uganda, Rwanda, Kenya, and Burundi) and quite different in DRC and Tanzania. This results would be compared with the update report of leprosy since it showed the increment of the recorded number for some countries (Uganda, Tanzania, and DRC) and decrement in Rwanda, unfortunately, some countries did not show their reports (Burundi and Kenya) [47]…”
Section: The Mean Differences Between Countries In New Cases and Deathsmentioning
confidence: 99%